Light‐Mediated Transfection of the Ocular Surface Using an Ophthalmic YAG Laser - Junho Byun; Mike Wels; Bernd Vanmeerhaeghe; Luca Paoletti; Tao Lu; Aranit Harizaj; Jonathan Tavernier; Dimitri Roels; Ilia Goemaere; Katrien Remaut; Koen Raemdonck; Kevin Braeckmans; et al. (Advanced Healthcare Materials, 2026)
ABSTRACT Diseases of the ocular surface, such as dry eye disease (DED), can significantly impair vision and reduce the quality of life. Current treatments rely primarily on conventional approaches, including artificial tears, antibiotics, and anti‐inflammatory drugs. However, advances in nucleic acid (NA) therapeutics have opened new avenues for treating ocular surface disorders, with growing interest in small interfering RNA (siRNA) and messenger RNA (mRNA) as potential drugs. A key challenge remains the efficient delivery of these macromolecules into cells of the ocular surface, where both extracellular and intracellular barriers hinder their cellular uptake and activity. To address this limitation, we explore the use of photoporation, a laser‐based physical transfection technique, to enhance mRNA delivery into ocular surface cells. Photoporation employs pulsed‐laser irradiation of photosensitizers to generate vapor nanobubbles (VNBs), whose rapid expansion and implosion produce mechanical forces that transiently permeabilize cell membranes, thereby promoting intracellular delivery of co‐administered nucleic acids. Using polydopamine nanoparticles (PD NPs) as biocompatible photosensitizers for photoporation, we demonstrate mRNA transfection in the corneal epithelium with both an experimental and a clinically approved pulsed‐laser system. Our results highlight the potential of laser‐based approaches for noninvasive engineering of the ocular surface.